Modification of pristine layered double hydroxide to form metal oxide composites as an anionic dye photodegradation catalysts - Yuliasari, Nova; Amri; Mohadi, Risfidian; Elfita; Lesbani, Aldes (Communications in Science and Technology, 2022)
Pristine layered double hydroxide (LDH) in the form of clay Mg/Al LDH was enhanced its catalytic ability by impregnating metal oxides to form Mg/Al-metal oxide composites in congo red (CR) degradation. The composite was calcined at a not high temperature of 300 oC and characterized using SEM and DRUV. In this report, the photodegradation of CR as anionic dye was optimized based on the variables of pH, catalyst weight and time radiation. The stability of the catalyst was studied from the percent degradation in the recycling test. The characterization of the catalyst that has undergone 5th regeneration cycles was carried out using XRD and FTIR. The results of this study revealed that catalysis by Mg/Al-metal oxide composites resulted in a better percent degradation, rate constant and materials stability than pristine Mg/Al LDH. Mg/Al LDH, Mg/Al-TiO2 and Mg/Al-ZnO catalyzed the photodegradation of CR by 65.97%, 73.06 % and 86.86%, respectively.